Benefits of the technical-vocational education and training for the Filipinos: An impact evaluation study - Abing, Martha Joy J. (Animo Repository, 2023)
The pressure for technical-vocational education and training (TVET) to deliver skilled and competent laborers has become a major concern in the labor market. As such, the strong desire of exploring the effectiveness of TVET's skills training programs on whether or not it has significantly benefit to the work and economic opportunities of the graduates needs to be conducted. Despite the growing number of alternative learning system (ALS) graduates, there is a limited literature on the employability of those who have completed TVET in comparison to those who have not pursued it. Therefore, this study aims to fill this gap by measuring the success of the TVET program completers in terms of their employment, job security and wages. Using the dataset of the World Bank STEP Skills Measurement Household Survey for the Philippines, 2015-2016, this study seeks to determine whether completing TVET has significantly increased the employability, job security and wages of the ALS graduates. Utilizing the method of propensity score matching (PSM), this study finds that ALS graduates who pursued and completed TVET are more likely to be employed, secure a stable job and get higher wages compared to those who have not. This result supports the findings of a similar study conducted by the Asian Development Bank (ADB) in 2021 that TVET showed a positive significant impact on employability and wages. This positive and significant effect of TVET on employment, job security and wages to ALS graduates who have completed TVET is validated by the use of coarsened exact matching (CEM) and fixed effect model, highlighting the robustness and reliability of the study’s methodology. Hence, this study concludes that TVET has a significant role in enhancing employment, job security and better pay for the ALS graduates in the Philippines. Keywords: TVET, ALS, employment, job security and wages